A Description of Lecithocladium angustiovum (Digenea: Hemiuridae) in Short Mackerel, Rastrelliger brachysoma (Scombridae), of Indonesia - Forcep Rio Indaryanto,; Muhamad Fadry Abdullah,; Yusli Wardiatno,; Risa Tiuria,; Hideyuki Imai, (Tropical Life Sciences Research, 2015)
Lecithocladium angustiovum is identified from the stomach (87.33%) and the intestine (12.67%) of Indonesian short mackerel (Rastrelliger brachysoma). The description includes an elongated body; a mean total length of 1018.84 ?m; and an ecsoma of 47.52% of the total length. The oral and ventral sucker ratio is 1:0.63, and the pharynx length is 97.42 ?m. The sequence results were obtained by 18s rDNA gene sequencing of the 354 basepair (bp) DNA segment, and the mean base composition (%) was 17.7 A; 35.7 T; 29.6 G; and 17.1 C. A phylogenetic tree was constructed to demonstrate the genetic distance between L. angustiovum and sequences from Lecithocladium excisum, Dinurus longisinus, Plerurus digitatus and Lecithochirium caesionis obtained from GenBank. Lecithocladium angustiovum dikenal pasti daripada perut (87.33%) dan usus (12.67%) ikan makerel Indonesia (Rastrelliger brachysoma). Deskripsi termasuk badan yang panjang; min panjang total sebanyak 1018.84 ?m; dan eksoma sebanyak 47.52% daripada panjang total. Nisbah penghisap oral dan ventral ialah 1:0.63, dan panjang farinks ialah 97.42 ?m. Keputusan jujukan didapati melalui penjujukan gen 18s rDNA untuk segmen DNA sebanyak 354 basepair (bp), dan komposisi min base (%) ialah 17.7 A; 35.7 T; 29.6 G; dan 17.1 C. Pokok filogenetik telah dikonstruksi untuk menunjukkan jarak genetik antara L. angustiovum dan jujukan-jujukan daripada Lecithocladium excisum, Dinurus longisinus, Plerurus digitatus dan Lecithochirium caesionis yang didapati dari GenBank.